Spontaneous evaluations: similarities and differences between the affect heuristic and implicit attitudes - Spence, Alexa; Townsend, Ellen (2008)
The affect heuristic and implicit attitudes are two separate concepts that have arisen within different literatures but that have a number of similarities. This paper compares these two constructs with the aim of clarifying exactly what they are and how these relate to one another. By comparing and contrasting the affect heuristic and implicit attitudes we conclude that the ‘affect pool’ of images tagged with feelings referred to within the affect heuristic literature may be equivalent to the construct of implicit attitudes. Further to this, the affect heuristic itself could be considered as a specific sub-type of spontaneous process that is driven by implicit attitudes. We propose that each of the implicit attitude and affect heuristic constructs could be further developed through the examination and comparison of existing literatures surrounding the other. Implications for future research are outlined.